(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article examines different types of democracy of antiquity through the prism of ideas about freedom, equality and justice. The work shows that in the New Age, the main components of liberal and social democracy, civil society, representative democracy, executive, legislative and judicial power arise and develop in society. Based on an analysis of the socialist ideas of the classics of Marxism-Leninism, the Soviet model of socialism, it is shown that it represents a historical attempt to build on the technical base of the economy of an industrial civilization without the proper civil maturity of society and systemic political democracy. The article compares the history of the emergence and development of democratic ideas and values ​​in Kazakhstan and Russia, the features of their democratic transformations, in which the diversity and content of social relations manifest themselves, adherence to group, hierarchical norms and values, the specificity of the development of civil society, the principles of a nationwide idea, ideology. Keywords: democracy, civilized society, industrial civilization, culture, ideology.